y =3 \sqrt x4 - 4x +e \cos(x)

pavelniyazov pavelniyazov    1   11.04.2019 17:32    0

Ответы
Vagapova1 Vagapova1  29.05.2020 07:29

Відповідь:

\frac{3x^2\sqrt[3]{x}}{7 }-4lnx+cosx*e^{cosx}

Покрокове пояснення:

y=\sqrt[3]{x^4} -\frac{4}{x}+e^{cosx}\\y'=\int\limits {\sqrt[3]{x^4} -\frac{4}{x}+e^{cosx}} \, dx=\frac{x^{\frac{4}{3}+1}}{\frac{4}{3}+1}-4lnx+cosx*e^{cosx}=\frac{x^{\frac{7}{3}}}{\frac{7}{3} }-4lnx+cosx*e^{cosx}=\frac{3x^{\frac{7}{3}}}{7 }-4lnx+cosx*e^{cosx}=\frac{3\sqrt[3]{x^7}}{7 }-4lnx+cosx*e^{cosx}=\frac{3x^2\sqrt[3]{x}}{7 }-4lnx+cosx*e^{cosx}

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика